Training characteristics related to (the changes in) durability in semiprofessional cyclists - Voet, J. G.; van Erp, T.; Viribay, A.; de Koning, J. J.; Lamberts, R: P. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To provide insights into a dose-response relationship between training and time-trial performance, as assessed in both a "fresh" and a "fatigued" state (durability), including proposed underlying factors for durability: gross efficiency and substrate oxidation (FatOx and CarbOx).